2001
DOI: 10.1111/1467-8659.00474
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution for Algebraic Curves and Surfaces using Wavelets

Abstract: This paper describes a multiresolution method for implicit curves and surfaces. The method is based on wavelets, and is able to simplify the topology. The implicit curves and surfaces are de ned as the zero-valued algebraic isosurface of a tensor-product uniform cubic Bspline. A w avelet multiresolution method that deals with uniform cubic Bsplines on bounded domains has been constructed. Further, the report explains how to set the unknown coe cients to produce the most compact object, how to recover the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Interpolation methods have been used by many to construct implicit representations for curves and surfaces [40][41][42][43]. To construct an approximate distance field for a set S, one could sample the distance to S with desired resolution and interpolate the results using B-splines, radial basis, or other convenient basis functions.…”
Section: Relation To Other Approachesmentioning
confidence: 99%
“…Interpolation methods have been used by many to construct implicit representations for curves and surfaces [40][41][42][43]. To construct an approximate distance field for a set S, one could sample the distance to S with desired resolution and interpolate the results using B-splines, radial basis, or other convenient basis functions.…”
Section: Relation To Other Approachesmentioning
confidence: 99%
“…See section 3.2 for a detailed definition. In a previous work [Esteve et al(2001)Esteve, Brunet, and Vinacua] it has been shown how to compute multiresolution representations from this kind of surfaces.…”
Section: Previous Workmentioning
confidence: 99%
“…As in [Vinacua et al(1998)Vinacua, Navazo, and Brunet] and [Esteve et al(2001)Esteve, Brunet, and Vinacu it is only necessary to define the scalar function on the voxels stabbed by the isosurface. These will form a set of voxels named Voxel Collection (see figure 4).…”
Section: Bspline-based Piecewise Algebraic Surfacesmentioning
confidence: 99%
“…Then a battery of filters [24] c The Eurographics Association and Blackwell Publishing Ltd 2005 are applied to fair the surface and approximate the central point of the hard voxels (in order to work with pre-calculated filters getting faster algorithms). From this surface, a multiresolution model can be constructed using the techniques that we describe in Esteve et al [25]. Figure 22 shows the final surface obtained with a discrete marching cubes algorithm and with the piecewise algebraic surface fitting and fairing algorithm from the relaxed discrete membrane of the teapot.…”
Section: Final Surface Constructionmentioning
confidence: 99%